ENGINEERING GEOLOGICAL AND GEOTECHNICAL EVALUATION ON SOFT SOIL IN JUNGKAT AREA WEST KALIMANTAN FOR SETTLEMENT AND BUCKLING ANALYSIS OF PILE FOUNDATION - , EAB KRENG HAV ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study area is located in the Jungkat in West Kalimantan. Based on the geological map of Singkawang area and geotechnical engineering evaluation, this area is mainly soft soil. This thesis aims to evaluate the engineering properties of soft soil to develop the design of pile foundation and select the appropriate type of pile to support the load of the machine generator. Furthermore, this study will determine the settlement and critical buckling load of pile, which has been selected. The analysis of this research has evaluated on geological and geotechnical conditions of the study area to understand about characteristic of soft soil foundation by finding the influence to engineering properties of soil to select the appropriate type of pile foundation. Moreover, the design of pile foundation has been done into two sections (circle and square section). For settlement analysis was performed by manual and model analysis (Plaxis analysis). In addition, the critical buckling load was calculated by using Euler and Davisson method based on the comparison of each end condition boundary of pile. As the results from geological and geotechnical evaluation, this area is covered by only one rock unit formation, which consists of mud, sand, gravel, locally calcareous and plant material. In addition, there are two main layers. The first layer is Silty Clay layer, and the second layer is Sand. The depth of this first layer is start from ground surface to 41 m. It has shown the most important factors that cause the influence to engineering properties that can affect to the pile foundations such as: low bearing capacity, excessive water content, high compressibility and long term settlement. The second layer is consisted of two types of soil (fine sand and medium sand), is a hard layer. The Pre-Stress Concrete pile was selected to design the ultimate bearing capacity, settlement, and critical buckling load in two sections (Circle and Square section). It has the total 44 m for length